The ultimatum game and expected utility maximization: In view of attachment theory - Shaul Almakias; Avi Weiss (Bar-Ilan University, Department of Economics, 2009)
In this paper we import a mainstream psycholgical theory, known as attachment theory, into economics and show the implications of this theory for economic behavior by individuals in the ultimatum bargaining game. Attachment theory examines the psychological tendency to seek proximity to another person, to feel secure when that person is present, and to feel anxious when that person is absent. An individual's attachment style can be classified along two-dimensional axes, one representing attachment avoidance and one representing attachment anxiety. Avoidant people generally feel discomfort when being close to others, have trouble trusting people and distance themselves from intimate or revealing situations. Anxious people have a fear of abandonment and of not being loved. Utilizing attachment theory, we evaluate the connection between attachment types and economic decision making, and find that in an Ultimatum Game both proposers' and responders' behavior can be explained by their attachment styles, as explained by the theory. We believe this theory has implications for economic behavior in different settings, such as negotiations, in general, and more specifically, may help explain behavior, and perhaps even anomalies, in other experimental settings.
Keywords: C91; C78; 330; Attachment Theory; Experimental Economics; Behavioral Economics; Ultimatum Game; Psychology and Economics; Ultimatumspiel; Experimentelle Ökonomik; Verhaltensökonomik